Influences of the Twisted Strips Insertion on the Performance of Flat Plate Water Solar Collector - Hassan, Jafar M.; Abdul-Ghafour, Qussai J.; Mohammed, Mohammed F. (Al-Khwarizmi Engineering Journal, 2015)
Abstract    In order to enhance the efficiency of flat plate solar water collectors without changing in its original shape and with low additional cost, twisted strips are inserted inside its riser pipes. Three flat plate collectors are used for test. Family of twisted strips are inserted inside each collector risers with different twisted ratios (TR=3,4,5). The collectors are connected in parallel mode (Z-Configuration) and are exposed to the same conditions (solar radiation and ambient temperature) .The experimental results show that, the highest heat transfer rate occurs at twisted ratio (3) .Consequently, for the same twisted ratio the daily efficiencies for the solar collector at different flow rate used (60,100 and 150) ℓ /hr. were 49 %, 57% and 63% respectively. Keywords: Twisted strip, solar collectors.